Penerapan Algoritma Gopala-Hemachandra Code2 (GH-2(n)) Pada Kompresi File Audio - Sinta M. Panjaitan; Surya Darma Nasution; Bister Purba (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2020)
Current technological developments are increasingly advanced which also have an impact on communication lines. The development is based on the emergence of the internet, through the internet, many things have been done, one of which is the exchange of information. However, this development creates new problems, namely due to the relatively large size so that it requires storage media to accommodate all the data received. From these problems, a technique was found in order to solve all the problems previously found. The technique is called the compression technique. is the process of converting the original (raw) data into another data stream with a different format that has a smaller size or the process of converting a set of data into coded form in order to save storage space. In this case, what I use in compression is the Gopala-Hemachandra Code 2 (GH-2 (n)) algorithm for compressing audio files. So from this research we will get what percentage of the data before the compression process is carried out with those that have been demcompressed. So that users can also save more storage space without losing information, besides that the time used in the transmission process will be less.Keywords: Compression1, Audio Files2, Gopala-Hemachandra Code 2 (GH-2 (n))2